PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI PADA PERUSAHAAN DELISTING DI BURSA EFEK INDONESIA (BEI) - Anggita Prameswari; Irni Yunita; Muhammad Azhari (JRAK, 2018)
This research aimed to understand how to use of the Altman Z-Score, Springate, and Zmijewski methods, to predict bankruptcy and help to analyze companies that have been delisted from Indonesian Stock Exchange in time period of 2011–2015. This research used descriptive method with quantitative approach. The population used in this research are companies that have been delisted in time period of 2011-2015, using the financial report from three years before the companies delisting from Indonesian Stock Exchange. Non-probability sampling with purposive sampling technique were used, with nine companies that have been delisted from Indonesian Stock Exchange. The result showed that there are different prediction from each methods. Most delisting companies are predicted to bankrupt at least one of the methods.